An optimal acquisition model for advanced manufacturing technology considering multiple objectives and timing of the acquisition - Zalatar, Willy Fernandez (Animo Repository, 1999)
Advanced Manufacturing Technologies (AMT), such as computer numerical control machines, robotics, and computer-aided design, have been developed in the past few years with the ultimate objective of optimizing production. This study aims to fill the research gap between the two major concerns in AMT acquisition which are the multi-attribute structure of the decision-making process and the timing of the acquisition. For this purpose, a nonlinear programming model is formulated with three objectives: net present value, flexibility, and quality. Given the multiple sequential technological innovations in the future which are predicted by the technological growth curve, the model solves for the optimal time(s) of acquisition and the optimal technology level(s) to acquire such that the benefits to be received by a firm are maximized. The study reveals that an acquisition tends to be justified earlier if little importance is given to net present value and more weight is given to flexibility and quality. Furthermore, the study also shows that if the technological improvement is high, the justification takes only a shorter time as compared to when the technological improvement is low.